Pedagogical curation: connecting young children’s learning with art museum curatorial practices - Penfold, Louisa (2019)
Young children under the age of five have become an increasingly important audience for art museums around the world with many institutions developing specialised activities, spaces and staff for this age group. However, curatorial practices for this audience differ significantly across the sector; there are diverse perspectives on how art museums can best support children’s learning and thus diverse offers. This thesis aimed to support a well-theorised curatorial practice that is focused on learning.